Pengaruh Physical Evidence, Tourist Attraction, Service Quality dan Aksesibilitas Terhadap Revisit Intention dengan Tourist Satisfaction sebagai Variabel Mediasi (Study Kasus pada Pengunjung Gatra Kencana Pemalang) - Diah Wuriah Ningsih; Linda; Santi Suciningtyas; Dian Murdianingsih (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2026)
This study aims to examine the influence of Physical Evidence, Tourist Attractions, Service Quality, and Accessibility on Revisit Intention, with Tourist Satisfaction as a mediating variable on tourists visiting the Gatra Kencana tourist attraction in Pemalang. The research approach uses a quantitative method supported by qualitative analysis, with a sample of 100 respondents determined through a purposive sampling technique. Data analysis was conducted using several test stages, including instrument testing, t-tests, path analysis, and sobel tests to test the mediation effect. The research findings indicate that all instruments used are valid and reliable. Partially, each independent variable, namely Physical Evidence, Tourist Attractions, Service Quality, and Accessibility, has a significant influence on Revisit Intention. In addition, Tourist Satisfaction is proven to have a mediating role that strengthens the relationship between the independent variables and tourists' revisit intentions. Thus, tourist satisfaction is an important factor that contributes to increasing tourists' desire to return to the Gatra Kencana tourist destination in Pemalang Keywords: physical evidence, tourist attraction, service quality, accessibility, revisit intention, tourist satisfaction